Translating Text of Cultural Terms in Mangupa A Mandailing Formal Traditional Marriage Counseling Ceremony - zainuddin zainuddin hasibuan (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
Mandailing is a region in North Sumatra one of province in Indonesia that has and preserves traditional culture. One of the specific aspects of traditional Mandailing culture is process of marriage. Mangupa as the final or Mandailing final marriage ceremony is a very interesting ceremony. It is delivered verbally and by using various kinds of objects as symbols which is realized in a relatively long text and uses many cultural words and expressions that require certain translation strategies and techniques. Objective of the research is to find out translation techniques which are used by the translator in transalting cultural terms of Mangupa into English and to explain how the quality of translation in transalting cultural terms of Mangupa into English. This research uses qualitative method which applies descriptive approach to assess data with documents and key informants as source of data. Research findings identifies that translation techniques used by the translator in transalting cultural terms of Mangupa into English consists of three technique. They are 11 data are single translation technique (18.64%), 36 data are couplet translation technique (61.01%), and 12 data are triplet translation technique (20.03%). The researcher analyzed 59 data of cultural terms which is found in the text Mangupa a formal traditional ceremony in Mandailing. The text Mangupa consists of 22 paragraphs and 37 in the form of verses. The quality of translation shows that The accurate translation consists of 42 data (71.18%) and less accurate translation is 17 data (28.18%). The acceptable translation is 47 data (79.66%) and less acceptable is 12 data (20.33%). The high readability translation is 30 data (50.84%) while medium readability translation is consist of 29 data (49.15%). It is identified that the quality of translation is accurate, acceptable and has a high degree of readability. It means that the quality of translation is very good.